Manufacturing method of powder for dust core
Patent Information
- Application Number
- JP2022149951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2042-09-21
Smart Images

Figure 0007633974000007 
Figure 0007633974000008 
Figure 0007633974000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a powder for dust cores obtained by mixing a soft magnetic powder with an inorganic insulating powder, and the powder for dust cores. [Background technology]
[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core, and this core is made of a powder magnetic core.
[0003] Powder cores are made by compressing powder for powder cores at a rate of several tons / cm 2 ~Several tens of tons / cm 2 This is done by pressing the powder compact under high pressure, and then subjecting the powder compact to a heat treatment called annealing. Annealing is carried out to remove distortion that occurs during press forming.
[0004] The powder for dust cores contains soft magnetic powder and inorganic insulating powder. The inorganic insulating powder is attached to the periphery of the soft magnetic powder. By attaching the inorganic insulating powder to the periphery of the soft magnetic powder, it is possible to insulate the soft magnetic powder particles from each other, and it becomes possible to increase the heat treatment temperature during annealing. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-145065 Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, there are cases where the inorganic insulating powder is not uniformly attached around the soft magnetic powder, i.e., the inorganic insulating powder clumps together and adheres to one place, or conversely, there are cases where the inorganic insulating powder does not adhere at all, leaving the surface of the soft magnetic powder exposed.
[0007] If the inorganic insulating powder is not uniformly attached, the fluidity of the soft magnetic powder deteriorates, and the mold is not filled to every corner, which affects the dimensional accuracy and weight of the powder core. In addition, when an insulating coating is formed using silicone resin or the like, the adhesion of the insulating coating also becomes unstable, which affects the magnetic properties. Furthermore, when the soft magnetic powder with the inorganic insulating powder attached thereto is heat-treated, the soft magnetic powder solidifies and must be broken down by hitting with a hammer or the like, which reduces productivity.
[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a method for producing a powder for a dust core in which an inorganic insulating powder uniformly adheres to the periphery of a soft magnetic powder, and a powder for a dust core. [Means for solving the problem]
[0009] The method for producing a powder for dust cores of the present invention includes a mixing step of adding a soft magnetic powder and an inorganic insulating powder to a mixing container and adhering the inorganic insulating powder to the periphery of the soft magnetic powder, the mixing step being carried out so that the soft magnetic powder and the inorganic insulating powder are dispersed and scattered in multiple directions in the mixing container rather than in one direction, and after the mixing step, the soft magnetic powder to which the inorganic insulating powder has been adhered has a coefficient of variation CV value obtained by dividing the standard deviation σ by the average value X, where X is the average oxygen content of the soft magnetic powder to which the inorganic insulating powder has been adhered, the average oxygen content of the soft magnetic powder to which the inorganic insulating powder has been adhered, the standard deviation being σ. 0.0169 or more 0.0229 The present invention is characterized by the following: Effect of the Invention
[0011] According to the present invention, a method for producing a powder for dust cores in which inorganic insulating powder is uniformly attached around soft magnetic powder, and a powder for dust cores can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic diagram showing a place where powder for dust cores was collected from a mixer. [Diagram 2] 1 is a graph showing the coefficient of variation CV values of Examples 1 to 4 and Comparative Example 1. [Diagram 3] 1A and 1B are SEM images at a magnification of 5000, where (a) is an SEM image of Example 2 and (b) is an SEM image of Comparative Example 1. [Figure 4] 1A is an SEM image of Example 2, and FIG. 1B is an SEM image of Comparative Example 1 at a magnification of 10,000. [Diagram 5] 1 is a graph showing the density of Examples 1 to 4 and Comparative Example 1. [Figure 6] 2 is a graph showing hysteresis loss, eddy current loss, and iron loss in Examples 1 to 4 and Comparative Example 1. [Figure 7] 1 is a graph showing the initial permeability μ0 and the permeability μ10k at 10 kA / m of Examples 1 to 4 and Comparative Example 1. [Figure 8] 1 is a graph showing the resistivity values of Examples 1 to 4 and Comparative Example 1. [Figure 9] 1 is a graph showing the rattler values of Examples 1A to 4A and Comparative Example 1A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Embodiment) The powder for dust core and the dust core according to the present embodiment will be described in detail below. Note that the present invention is not limited to the embodiment described below.
[0014] Powder cores are magnetic materials used in the cores of coil parts installed in office equipment, solar power generation systems, automobiles, etc. Powder cores are made by compressing powder for powder cores and annealing it. Powder for powder cores includes soft magnetic powder and inorganic insulating powder. Powder for powder cores is made by mixing soft magnetic powder and inorganic insulating powder, with the inorganic insulating powder uniformly attached around the soft magnetic powder.
[0015] The powder for dust cores is surrounded by an insulating coating made of an insulating material. The powder for dust cores covered with this insulating coating is compressed into a powder compact, which is then annealed to produce the dust core.
[0016] The soft magnetic powder is mainly composed of iron. As the soft magnetic powder, pure iron powder, permalloy (Fe-Ni alloy) mainly composed of iron, Si-containing iron alloy (Fe-Si alloy), sendust alloy (Fe-Si-Al alloy), or a mixture of two or more of these powders can be used. In addition, amorphous alloy and nanocrystalline alloy powder can be used as the soft magnetic powder. The particle size (median size D50) of the soft magnetic powder is preferably 1 μm or more and 200 μm or less.
[0017] The Fe-Si-Al alloy powder contains, for example, about 7 wt% to 11 wt% of Si and about 4 wt% to 8 wt% of Al relative to Fe. The Fe-Si-Al alloy powder may contain, for example, about 1 wt% to 3 wt% of Ni relative to Fe. Furthermore, the Fe-Si-Al alloy powder may contain Co, Cr, or Mn.
[0018] The Si-containing iron alloy may contain Co, Al, Cr, or Mn. When using permalloy (Fe-Ni alloy), the ratio of Ni to Fe is preferably 50:50 or 25:75, but may be other ratios. For example, Fe-80Ni, Fe-36Ni, Fe-78Ni, or Fe-47Ni may be used. In addition to Fe and Ni, Si, Cr, Mo, Cu, Nb, Ta, etc. may be contained. Examples of Fe-Si alloy powder include Fe-3.5%Si alloy powder and Fe-6.5%Si alloy powder, but the ratio of Si to Fe may be other than 3.5% or 6.5%. Pure iron powder contains Fe at 99% or more.
[0019] The inorganic insulating powder adheres to the periphery of the soft magnetic powder. By adhering the inorganic insulating powder to the periphery of the soft magnetic powder, the soft magnetic powder can be insulated from each other. The inorganic insulating powder adheres uniformly to the periphery of the soft magnetic powder. "Uniform" here means that the inorganic insulating powder is adhered to the periphery of the soft magnetic powder evenly and in about the same amount. In other words, it means that the inorganic insulating powder is not aggregated and clumped together, or that the inorganic insulating powder is not attached and the surface of the soft magnetic powder is not exposed. Whether or not the powder is adhered uniformly can be confirmed by observing the powder at 5000 or 10000 times magnification with an electron microscope or by checking whether the coefficient of variation CV value described later is 0.023 or less.
[0020] The inorganic insulating powder adheres uniformly to the periphery of the soft magnetic powder, improving the fluidity of the powder for dust cores, increasing density, and reducing hysteresis loss. In addition, the inorganic insulating powder ensures a distance between the soft magnetic powder particles, and the binder effect of the insulating materials such as silicone resin and silane coupling agent that make up the insulating coating is improved, resulting in extremely high strength.
[0021] When the inorganic insulating powder aggregates and adheres unevenly around the soft magnetic powder, there is a risk that the insulating material will not adhere to the aggregated area or that the amount of the insulating material adhered thereto will be small. If the amount of the insulating material adhered thereto is small, the binding strength between the soft magnetic powder particles in that area will be weak, making the core more susceptible to chipping or cracking.
[0022] On the other hand, when the inorganic insulating powder is uniformly attached to the periphery of the soft magnetic powder as in the present embodiment, it is possible to suppress the occurrence of areas where the insulating material is not attached or where the amount of attached insulating material is small around the soft magnetic powder (strictly speaking, around the inorganic insulating powder attached around the soft magnetic powder). Therefore, the binding force between the soft magnetic powder particles is increased, and the strength is increased. This makes it possible to prevent chipping and cracking of the core.
[0023] The inorganic insulating powder may be alumina powder, magnesia powder, silica powder, titania powder, zirconia powder, etc. The particle size of the inorganic insulating powder is smaller than that of the soft magnetic powder. The particle size (median size D50) of the inorganic insulating powder is preferably 7 nm or more and 200 nm or less.
[0024] The coefficient of variation CV of a powder in which inorganic insulating powder is attached to the periphery of soft magnetic powder (hereinafter also referred to as "mixed powder") is 0.023 or less. The coefficient of variation CV is measured by sampling the mixed powder from multiple locations in a mixing container and measuring the amount of oxygen at each location. The average value X and standard deviation σ of the oxygen amount are calculated from each measurement result. The coefficient of variation CV is then calculated by dividing the standard deviation σ by the average value X.
[0025] The locations from which the oxygen is sampled are not limited to the above, but are taken from five locations on the top surface of the mixing vessel. The five locations are, for example, the center of the circular mixer ((1) in FIG. 1) and four equally spaced locations along the circumferential direction ((2) to (5) in FIG. 1, which are the 12 o'clock, 3 o'clock, 6 o'clock, and 9 o'clock positions on a clock), as shown in FIG. 1. In this way, by measuring the amount of oxygen in the mixed powder at multiple dispersed locations, rather than at one location, an accurate coefficient of variation (CV) value can be calculated.
[0026] If the mixer is rectangular, the sample may be collected from a total of five locations, including the center and each vertex. Also, instead of collecting samples from the top surface of the mixing vessel, samples may be collected from the bottom surface or the center between the top and bottom surfaces of the mixing vessel, or samples may be collected from multiple locations each from the top surface, bottom surface, and center.
[0027] An insulating coating is formed around the powder for dust cores. The insulating coating is made of an insulating material. As the insulating material, a silane compound, a silicone resin, or a silicone oligomer can be used. In addition, the insulating material used as the insulating coating may be one type or two or more types. When two or more types are used, each type of insulating coating layer may be laminated, or a single layer of two or more types of insulating materials may be mixed. That is, for example, when a silane compound and a silicone resin are used, an insulating coating layer made of a silane compound may be formed around the powder for dust cores, and an insulating coating layer made of a silicone resin may be formed around this insulating coating layer, or a single layer insulating coating layer made of a mixture of a silane compound and a silicone resin may be formed.
[0028] The silane compound includes a silane compound without a functional group and a silane coupling agent. As the silane compound without a functional group, for example, an alkoxysilane such as an ethoxy type or a methoxy type can be used, and tetraethoxysilane is particularly preferred. As the silane coupling agent, an aminosilane type, an epoxysilane type, or an isocyanurate type silane coupling agent can be used, and 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, or tris-(3-trimethoxysilylpropyl)isocyanurate is particularly preferred.
[0029] The amount of the silane compound added is preferably 0.05 wt% or more and 1.0 wt% or less of the soft magnetic powder. By setting the amount of the silane compound added in this range, the fluidity of the soft magnetic powder can be improved, and the density, magnetic properties, and strength properties of the compacted powder core can be improved.
[0030] Silicone resin is a resin that has a siloxane bond (Si-O-Si) in its main skeleton. By using silicone resin, it is possible to form a coating with excellent flexibility. Silicone resins that can be used include methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, and rubber-based silicone resins. Among these, when using methylphenyl-based silicone resins in particular, it is possible to form an insulating coating with little loss in weight when heated and excellent heat resistance.
[0031] The amount of silicone resin added is preferably 0.6 wt% or more and 2.5 wt% or less relative to the soft magnetic powder. If the amount added is less than 0.6 wt%, it will not function as an insulating coating, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.5 wt%, it will result in a reduction in the density of the powder magnetic core.
[0032] As the silicone oligomer, methyl-based or methylphenyl-based ones having an alkoxysilyl group and no reactive functional group, epoxy-based, epoxymethyl-based, mercapto-based, mercaptomethyl-based, acrylic methyl-based, methacrylic methyl-based, vinylphenyl-based ones having an alkoxysilyl group and a reactive functional group, or alicyclic epoxy-based ones having a reactive functional group instead of an alkoxysilyl group, etc. can be used. In particular, by using a methyl-based or methylphenyl-based silicone oligomer, a thick and hard insulating coating can be formed. In addition, in consideration of the ease of forming the insulating coating, methyl-based or methylphenyl-based ones having a relatively low viscosity may be used.
[0033] The amount of silicone oligomer added is preferably 0.1 wt% or more and 2.0 wt% or less of the soft magnetic powder. If the amount added is less than 0.1 wt%, it will not function as an insulating coating, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.0 wt%, it will result in a decrease in the density of the powder core.
[0034] When forming an insulating coating around the powder for dust core, pure water may be added in addition to the insulating material, which promotes the reaction of the insulating material.
[0035] The powder for the dust core with the insulating coating formed thereon is filled into a die and compacted under a prescribed pressure to form a dust compact, which is then annealed to form a dust core.
[0036] Next, a method for producing the powder for dust cores and the dust cores will be described. The method for producing the powder for dust cores includes a mixing step. The method for producing the dust cores includes a powder heat treatment step, an insulating coating formation step, a lubricant addition step, a compaction step, and an annealing step.
[0037] The mixing process is a process in which the soft magnetic powder and the inorganic insulating powder are added to a mixing container and mixed. In the mixing process, the soft magnetic powder and the inorganic insulating powder are mixed so that they scatter in all directions. That is, the soft magnetic powder and the inorganic insulating powder move around in the mixing container not only in a certain direction but also in many directions. For example, a semispherical elastic member (e.g., a rubber ball, etc.) having flexibility may be provided on the bottom surface of the mixing container, and the mixing container may be rocked and the elastic member may be rotated to scatter the soft magnetic powder and the inorganic insulating powder in all directions by utilizing the expansion and contraction of the elastic member. In addition, the mixing container may be rotated eccentrically in an irregular manner to scatter the soft magnetic powder and the inorganic insulating powder in all directions. Through the mixing process, the inorganic insulating powder adheres uniformly to the periphery of the soft magnetic powder.
[0038] The mixing time is preferably 2 minutes or more and 20 minutes or less, and more preferably 5 minutes or more and 20 minutes or less. By setting the mixing time in this range, the inorganic insulating powder adheres uniformly around the soft magnetic powder, and the coefficient of variation CV value is 0.023 or less. In general, it seems that the longer the mixing time, the more uniform the adhesion will be, but if the mixing time is long, further aggregated inorganic insulating powder will be generated around the uniformly adhered inorganic insulating powder, which may result in non-uniform adhesion.
[0039] In addition, the present invention is more effective when the particle diameter of the soft magnetic powder is 1 μm or more and 200 μm or less, and the particle diameter of the inorganic insulating powder is 7 nm or more and 200 nm or less. In particular, the effect is more pronounced when the particle diameter of the soft magnetic powder is a small powder of 1 μm or more and 5 μm or less, and the particle diameter of the inorganic insulating powder is 7 nm or more and 200 nm or less.
[0040] For example, when mixing soft magnetic powder with a size of more than 5 μm and less than 200 μm with inorganic insulating powder with a size of 7 nm to 200 nm, if it is not possible to disperse in multiple directions as with a conventional V-type mixer, the particle size difference is large and only the inorganic insulating powder will aggregate. On the other hand, by dispersing in all directions as in this embodiment, that is, in multiple directions instead of in one direction, it is possible to prevent the inorganic insulating powder from aggregating.
[0041] Furthermore, when mixing small soft magnetic powder with a particle size of 1 μm to 5 μm with inorganic insulating powder with a particle size of 7 nm to 200 nm, the nano-sized inorganic insulating powder will undergo primary and secondary aggregation between the soft magnetic powder particles and the inorganic insulating powder particles due to van der Waals forces. However, as in this embodiment, the primary and secondary aggregation can be suppressed by dispersing the soft magnetic powder particles omnidirectionally, that is, in multiple directions instead of in one direction.
[0042] After the mixing step, the powder undergoes a powder heat treatment step. The powder heat treatment step is a step of heat treating the powder for dust core. That is, it is a step of heat treating the soft magnetic powder with inorganic insulating powder attached to the periphery. In the powder heat treatment step, the powder is heated in a non-oxidizing atmosphere for 1 to 6 hours. The non-oxidizing atmosphere includes a low oxygen atmosphere such as 0.01% in the atmosphere, an inert gas atmosphere, or a reducing gas atmosphere. Examples of the inert gas include noble gases such as Ar and N2. Examples of the reducing gas include H2. The heat treatment temperature is 400°C or higher and 1200°C or lower.
[0043] The insulating coating forming process is a process for forming an insulating coating around the powder for powder cores. In the insulating coating process, an insulating material is added to and mixed with the powder for powder cores. After mixing the insulating material, the mixture is heated and dried to form an insulating coating around the powder for powder cores. The heating and drying conditions are not limited to the following, but the mixture is dried at a temperature of 25°C or higher and 350°C or lower for about 2 hours.
[0044] The lubricant addition step is a step of adding a lubricant to the powder for powder cores on which the insulating coating has been formed. Examples of lubricants include, but are not limited to, stearic acid and its metal salts, as well as ethylene bisstearamide, ethylene bisstearamide, and ethylene bisstearamide. The amount of lubricant added is preferably about 0.2 wt% to 0.8 wt% of the powder for powder cores. By setting the amount within this range, it is possible to further improve the sliding between the powder for powder cores.
[0045] The compaction process is a process for producing a compact by compacting the powder for the powder core to which the lubricant has been added. First, the powder for the powder core is filled into a die, and then, a pressure of 5 to 20 ton / cm is applied. 2 In this manner, a powder compact is produced.
[0046] The annealing process is a process in which the powder compact produced through the pressure molding process is annealed to remove distortion in the soft magnetic powder. In the annealing process, the powder compact is heat-treated in a non-oxidizing atmosphere such as nitrogen gas, hydrogen gas, a mixture of nitrogen and hydrogen, or a low-oxygen atmosphere of about 0.01%, at a temperature of 600°C or higher and lower than the temperature at which the insulating coating formed around the soft magnetic powder is destroyed (for example, 900°C). By undergoing this annealing process, a powder magnetic core is produced.
[0047] (Example) The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. Powders for dust cores and dust cores of Examples 1 to 4 and Comparative Example 1 were produced.
[0048] First, a powder for a dust core was prepared according to Example 1. Pure iron powder with an average particle size of 43 μm was used as the soft magnetic powder, and Al2O3 powder (alumina powder) with an average particle size of 13 nm was used as the inorganic insulating powder. The Al2O3 powder was used in an amount of 1.0 wt% relative to the pure iron powder.
[0049] The pure iron powder and Al2O3 powder were added to a oscillating mixer (Chiyoda Machinery Co., Ltd., OM30SA) and mixed. In this oscillating mixer, the pure iron powder and Al2O3 powder were mixed while scattering in all directions inside the mixing container. The mixing time was 5 minutes. In this way, the powder for dust core of Example 1 was produced.
[0050] The powders for dust cores in Examples 2 to 4 differ only in the mixing time from Example 1, and other materials, production procedures, and production conditions are the same as those in Example 1. The mixing times are 10 minutes in Example 2, 15 minutes in Example 3, and 20 minutes in Example 4.
[0051] In Comparative Example 1, similarly to Example 1, pure iron powder with an average particle size of 43 μm was used as the soft magnetic powder, and Al2O3 powder with an average particle size of 13 nm was used as the inorganic insulating powder. The Al2O3 powder was used at 1.0 wt% relative to the pure iron powder. Then, the pure iron powder and Al2O3 powder were added to a V-type mixer (Tokuju Machine Works, Ltd., V-60) and mixed. Since it is a V-type mixer, the pure iron powder and Al2O3 powder are mixed by moving only in a certain direction inside the mixer. In other words, in Comparative Example 1, the pure iron powder and Al2O3 powder are not scattered in all directions. The mixing time is 5 minutes. In this way, the powder for the dust core of Comparative Example 1 was produced.
[0052] The powders for dust cores produced in Examples 1 to 4 and Comparative Example 1 were sampled from the mixer, and the oxygen content was measured. In each of Examples 1 to 4 and Comparative Example 1, powders for dust cores were sampled from five locations on the top surface of the mixer. As shown in FIG. 1, samples were taken from the center of the circular mixer ((1) in FIG. 1) and from four locations equally spaced along the circumferential direction ((2) to (5) in FIG. 1). The amount sampled was 50 g from each location. In Comparative Example 1, a V-shaped mixer was used, so the powder was transferred to a circular container and sampled from the locations (1) to (5) shown in FIG. 1.
[0053] The amount of oxygen was measured using an oxygen and nitrogen analyzer (TC500, manufactured by LECO). For the measurement, 0.1 g of the collected powder for dust cores was placed in a carbon crucible and heated at 2000°C, and the amount of oxygen was calculated for the generated CO or CO2 gas by infrared absorption. The amount of oxygen was measured for each of the powder for dust cores collected at five locations, and the average value X and standard deviation σ were calculated. Furthermore, the standard deviation σ was divided by the average value X to calculate the coefficient of variation CV. In Examples 1 to 4 and Comparative Example 1, the amount of oxygen was measured at five locations, and the average value X, standard deviation σ, and coefficient of variation CV were calculated.
[0054] The calculated results are shown in Table 1. Moreover, a graph of the coefficient of variation CV values of Examples 1 to 4 and Comparative Example 1 is shown in FIG. [Table 1]
[0055] As shown in Table 1 and FIG. 2, the coefficient of variation CV values of Examples 1 to 4 in which the pure iron powder and Al2O3 powder were scattered in all directions were 0.023 or less, which is smaller than the CV of Comparative Example 1, which was 0.0278, by about 0.005.
[0056] Furthermore, in order to confirm the adhesion of the Al2O3 powder to the pure iron powder in the collected dust core powders in Example 2 and Comparative Example 1, the powders were observed using a field emission scanning electron microscope (JSM-7001F manufactured by JEOL Ltd.) A predetermined amount of the powder was dispersed and attached to carbon tape, and a secondary electron image was observed and photographed at 10 kV in a vacuum atmosphere.
[0057] The photographing results are shown in Figures 3 and 4. Figure 3 is an SEM image at a magnification of 5000, where (a) is an SEM image of Example 2 and (b) is an SEM image of Comparative Example 1. Figure 4 is an SEM image at a magnification of 10000, where (a) is an SEM image of Example 2 and (b) is an SEM image of Comparative Example 1. In each SEM image, the white portion indicates Al2O3 powder.
[0058] As shown in Figures 3(a) and 4(a), in Example 2, the white parts are not concentrated in one place, and the Al2O3 powder is uniformly dispersed around the pure iron powder. On the other hand, in Comparative Example 1, as shown by the black circles in Figures 3(b) and 4(b), white lumps are scattered, and the Al2O3 powder is aggregated. Therefore, when the pure iron powder and the Al2O3 powder are mixed so that they scatter in all directions, the coefficient of variation CV value becomes 0.023 or less, and it was confirmed that the Al2O3 powder adheres uniformly.
[0059] 2, the coefficient of variation CV value reaches a lower limit peak around Examples 2 and 3, and the coefficient of variation CV value increases in Example 4 where the mixing time is 20 minutes. From this, it was confirmed that it is better to set the mixing time to 5 minutes or more and 20 minutes or less, rather than to perform the mixing for a long time.
[0060] Powder magnetic cores were then produced using the powders for powder magnetic cores of Examples 1 to 4 and Comparative Example 1. The powder magnetic cores of Examples 1 to 4 and Comparative Example 1 were produced by the same method as described below.
[0061] After mixing the pure iron powder and Al2O3 powder, the powder for the dust core was subjected to a powder heat treatment. The powder heat treatment was performed at 1000°C in a non-oxidizing atmosphere in which a mixed gas of hydrogen and nitrogen was injected. The heat treatment time was 2 hours.
[0062] After the powder was heat-treated, silicone resin and a silane coupling agent were added to form an insulating coating around the powder for the dust core. 1.8 wt% of silicone resin was added to the pure iron powder, and 0.5 wt% of silane coupling agent was added to the pure iron powder, and mixed for 1 minute. Then, 0.5 wt% of pure water was added to the pure iron powder, and mixed for another minute. The mixture was then exposed to a dryer maintained at 180°C for 2 hours, heated and dried, and an insulating coating was formed.
[0063] After forming the insulating coating, the powder for the dust core was cooled to room temperature and sieved through a sieve with 850 μm openings for crushing purposes. A lubricant was then added and mixed for 1 minute. Zinc stearate was used as the lubricant. The lubricant was added at 0.5 wt% relative to the pure iron powder.
[0064] After mixing with the lubricant, the powder for the dust core to which the lubricant was added was filled into a die and pressed to produce a toroidal powder compact with an outer diameter of 20.97 mm, an inner diameter of 12.48 mm, and a height of 4.8 mm. The pressure for the press molding was 9.5 ton / cm. 2 So I went.
[0065] After press molding, the density of the powder compacts of Examples 1 to 4 and Comparative Example 1 was measured. Density (kg / m 3 ) is the apparent density. The outer diameter, inner diameter, and height of the powder core are measured, and the volume of the powder compact (m 3 ) into π×(outer diameter 2 -Inner diameter 2 The weight of the powder magnetic core was then measured, and the density was calculated by dividing the measured weight by the calculated volume.
[0066] The calculation results are shown in Table 2. Moreover, a graph of the densities of Examples 1 to 4 and Comparative Example 1 is shown in FIG. [Table 2]
[0067] 5, the densities of Examples 1 to 4 are equal to or higher than that of Comparative Example 1. Specifically, only Example 3 had the same density as Comparative Example 1, but it was confirmed that Examples 1, 2, and 4 had improved densities compared to Comparative Example 1.
[0068] Furthermore, each of the powder compacts of Examples 1 to 4 and Comparative Example 1 was annealed to remove distortion caused by press molding. The annealing was performed at 620°C in a non-oxidizing atmosphere injected with a mixed gas of hydrogen and nitrogen. The heat treatment time was 2 hours. In this manner, each of the powder magnetic cores of Examples 1 to 4 and Comparative Example 1 was produced.
[0069] For the dust cores of Examples 1 to 4 and the Comparative Example, the core loss, magnetic permeability, resistivity, and rattle value were measured.
[0070] When measuring the iron loss, 30 turns of φ0.5 mm copper wire were wound around the powder magnetic core as the primary winding and 30 turns as the secondary winding. Then, using a BH analyzer (Iwatsu Measurement Corporation: SY-8219), which is a magnetic measuring device, the iron loss Pcv (kW / m 3 ) was measured. The hysteresis loss Phv (kW / m 3 ) and eddy current loss Pev (kW / m 3 ) was calculated. Hysteresis loss Phv (kW / m 3 ) and eddy current loss Pev (kW / m 3 ) was performed by calculating the hysteresis loss coefficient (Kh) and eddy current loss coefficient (Ke) from the frequency curve of iron loss Pcv using the following equations (1) to (3) by the least squares method.
[0071] Pcv = Kh×f + Ke×f 2 (1) Phv = Kh × f (2) Pev = Ke x f2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Phv: Hysteresis loss Pev: Eddy current loss
[0072] The measurement results are shown in Table 3. Moreover, Fig. 6 shows graphs of the hysteresis loss, eddy current loss, and iron loss of Examples 1 to 4 and Comparative Example 1. In the bar graph of Fig. 6, the black bars indicate the hysteresis loss. [Table 3]
[0073] As shown in Table 3 and FIG. 6, the eddy current loss in Examples 1 to 4, in which the Al2O3 powder was uniformly attached, was 100 (kW / m 3 In addition, the hysteresis loss is reduced by about 150 to 200 (kW / m) in Examples 1 to 4 compared to Comparative Example 1. 3 In this way, in Examples 1 to 4, the eddy current loss and the hysteresis loss are both reduced by about 100 (kW / m 3 ), resulting in a significant reduction in iron loss of 200 (kW / m 3 ) was significantly reduced. In other words, the effect of uniformly attaching the Al2O3 powder was evident.
[0074] The magnetic permeability was measured by winding two copper wires of φ0.5 mm in parallel around the powder magnetic core for 30 turns, and then using an LCR meter (Hewlett Packard, 4284A) to measure the initial magnetic permeability μ0 at 0 A / m and the magnetic permeability μ10k at 10 kA / m from the inductance of the magnetic field strength at 20 kHz and 1.0 V.
[0075] The measurement results are shown in Table 4. Fig. 7 shows a graph of the initial magnetic permeability μ0 and the magnetic permeability μ10k at 10 kA / m of Examples 1 to 4 and Comparative Example 1. In the bar graph of Fig. 7, the black bars indicate the initial magnetic permeability μ0. [Table 4]
[0076] 7, in Examples 1 to 4 in which the Al2O3 powder is uniformly attached, both the initial magnetic permeability μ0 and the magnetic permeability μ10k at 10 kA / m are improved compared to Comparative Example 1. In particular, in Examples 1 to 4, the distance between the pure iron powder particles is uniformly ensured by the Al2O3 powder, and minute gaps are formed, so that the magnetic permeability μ10k at 10 kA / m when overlapped is 32.5 or more, which is significantly improved compared to Comparative Example 1.
[0077] The resistivity value was measured using a resistivity meter (Loresta-GX MCP-T700, manufactured by Nitto Seiko Analytech Co., Ltd.) using a four-probe method to measure the circular surface of the toroidal core at four equally spaced locations on the circumference, and the average of the four measurement results was calculated.
[0078] The calculation results are shown in Table 5. Moreover, a graph of the resistivity values of Examples 1 to 4 and Comparative Example 1 is shown in FIG. [Table 5]
[0079] As shown in Table 5 and FIG. 8, Examples 1 to 4 have significantly higher resistivity values than Comparative Example 1. As described above, the eddy current loss in Examples 1 to 4 is 100 (kW / m 3 ) and it can be inferred that the uniform adhesion of the Al2O3 powder results in an improved resistivity and reduced eddy current loss.
[0080] Next, each of the powder compacts of Examples 1A to 4A and Comparative Example 1A was produced. The materials, production steps, and production conditions used for Examples 1A to 4A and Comparative Example 1A were the same as those of Examples 1 to 4 and Comparative Example 1, respectively, up to the step of adding the lubricant. For example, for Example 1A, the same materials, steps, and conditions were used as in Example 1 up to the step of adding the lubricant.
[0081] For each sample of Examples 1A to 4A and Comparative Example 1A, a lubricant was mixed, the mixture was filled into a die, and press-molded to produce a cylindrical powder compact having an outer diameter of 11.3 mm and a height of 10 mm. The pressure for press molding was 9.0 ton / cm. 2 In this manner, the powder compacts of Examples 1A to 4A and Comparative Example 1A were produced.
[0082] The rattler value was then measured. A rattler device (manufactured by INTESUKO) was used to measure the rattler value. The rattler value was measured based on the rattler value measurement method for metal powder compacts (JPMA P11 1992) of the Japan Powder Metallurgy Association (JPMA). That is, the core was placed in a cylindrical cage covered with a stainless steel wire mesh with an opening of 1180 μm, and rotated 1000 times at a rotation speed of 87 rpm. Thereafter, the weight of the green compact was measured, and the weight was subtracted from the weight measured before the rotation to obtain the mass reduction rate, thereby calculating the rattler value.
[0083] The calculation results are shown in Table 6. Moreover, Fig. 9 shows a graph of the rattler values of Examples 1A to 4A and Comparative Example 1A. [Table 6]
[0084] 9, the rattler values of Examples 1A to 4A were about 1 / 5 of that of Comparative Example 1A, and it was confirmed that the strength was significantly increased. Therefore, by uniformly attaching Al2O3 powder to pure iron powder, a dust core with improved strength can be manufactured, and it can be used for coil parts such as reactors that require high vibration resistance for use in vehicles.
[0085] As described above, Examples 1 to 4 have results at least equal to or better than Comparative Example 1 in each measurement item. In particular, the rattler value is significantly reduced to about 1 / 5 of Comparative Example 1A, and strength is improved. It is believed that the pure iron powder and Al2O3 powder are dispersed and scattered in all directions, and the Al2O3 powder is uniformly attached around the pure iron powder, improving the flowability of the powder and allowing the powder to reach every corner of the mold, thereby improving strength.
[0086] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.
Claims
1. A mixing step of adding a soft magnetic powder and an inorganic insulating powder to a mixing vessel and adhering the inorganic insulating powder to the periphery of the soft magnetic powder, The mixing step includes mixing the soft magnetic powder and the inorganic insulating powder so that the soft magnetic powder and the inorganic insulating powder are dispersed and scattered in all directions within a mixing container, After the mixing step, the soft magnetic powder to which the inorganic insulating powder is attached has a coefficient of variation CV value obtained by dividing the standard deviation σ by the average value X, where X is an average value of the oxygen content of the soft magnetic powder to which the inorganic insulating powder is attached, the average value being taken from a plurality of points on the top surface of a mixing container, and σ is a standard deviation of the oxygen content of the soft magnetic powder to which the inorganic insulating powder is attached, of 0.0169 or more and 0.0229 or less. A method for producing powder for dust cores, comprising the steps of:
2. The mixing vessel is provided with a semi-spherical elastic member having flexibility on a bottom surface, the mixing step includes rocking the mixing container and rotating the elastic member, and utilizing the expansion and contraction of the elastic member, the soft magnetic powder and the inorganic insulating powder are dispersed and scattered in all directions within the mixing container; The method for producing a powder for dust core according to claim 1,
3. The mixing step includes: rotating the mixing vessel irregularly and eccentrically; The method for producing a powder for dust core according to claim 1 or 2,
4. In the mixing step, the mixing time is 5 minutes or more and 20 minutes or less. The method for producing a powder for dust core according to claim 1 or 2,
5. In the mixing step, the mixing time is 5 minutes or more and 20 minutes or less. The method for producing a powder for dust core according to claim 3,
6. The particle size of the soft magnetic powder is 1 μm or more and 200 μm or less, The particle size of the inorganic insulating powder is 7 nm or more and 200 nm or less; The method for producing a powder for dust core according to claim 1 or 2,
7. The particle size of the soft magnetic powder is 1 μm or more and 200 μm or less, The particle size of the inorganic insulating powder is 7 nm or more and 200 nm or less; The method for producing a powder for dust core according to claim 3,
Citation Information
Patent Citations
Method of kneading ceramic material
JP1994226730A
powder mixer
JP1995000521U
Dust core and method of manufacturing the same
JP2010251474A
Dust core
JP2021145065A
Dust core and process for producing same
WO2011077601A1